2002
DOI: 10.1002/1099-0690(200206)2002:11<1750::aid-ejoc1750>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

exo/endoPreferences of Double Bonds in Three-Membered Ring Compounds − The Bias Toward Endocyclic Unsaturation in 3-Alkyl- and 3-Amino-2H-azirines: A Theoretical and Experimental Study

Abstract: Keywords: Ab initio calculations / Nitrogen heterocycles / Photolysis / Small ring systems / TautomerismIrradiation of the amino-4H-1,2,3-triazoles 7 (λ Ն 280 nm) affords molecular nitrogen and 3-amino-2H-azirines 8 in high yields. As shown on the basis of spectroscopic evidence, the photoproduct of 7a exists exclusively as 3-amino-2H-azirine 8a rather than in an equilibrium with the hypothetical iminoaziridine 10. Ab initio quantum chemical calculations up to the Gaussian-3 level were performed for pairs of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…It should be possible to transfer this concept from the hydrocarbons 1 to the heterocycles 3 2. 3 The 2,3‐bridged azirine 3 d , which is easily obtainable from azide 2 d by photolysis or thermolysis, can be distilled in vacuo,4 whereas the more unstable compound 4 could be characterized only in solution 5. Until now, the even more strained azirine 3 b and many similar bridged azirines bearing a six‐membered ring can be generated only in situ and detected by trapping reactions 4a.…”
Section: Methodsmentioning
confidence: 99%
“…It should be possible to transfer this concept from the hydrocarbons 1 to the heterocycles 3 2. 3 The 2,3‐bridged azirine 3 d , which is easily obtainable from azide 2 d by photolysis or thermolysis, can be distilled in vacuo,4 whereas the more unstable compound 4 could be characterized only in solution 5. Until now, the even more strained azirine 3 b and many similar bridged azirines bearing a six‐membered ring can be generated only in situ and detected by trapping reactions 4a.…”
Section: Methodsmentioning
confidence: 99%
“…Diese Betrachtungen sollten sich von den Kohlenwasserstoffen 1 auch auf die Heterocyclen 3 übertragen lassen 2. 3 Während das durch Photolyse oder Thermolyse aus dem Azid 2 d leicht zugängliche 2,3‐verbrückte Azirin 3 d im Vakuum destilliert werden kann,4 gelingt die Charakterisierung des instabileren Derivats 4 nur noch in Lösung 5. Das noch gespanntere Azirin 3 b und zahlreiche ähnliche, einen Sechsring aufweisende verbrückte Azirine ließen sich bisher nur in situ erzeugen und durch Abfangreaktionen nachweisen 4a.…”
Section: Methodsunclassified
“…The sophisticated G3 level of theory has been used to calculate the relative energies of a series of compounds based on 13 and 14 (X = CH 2 , NH and O). 16 It was found that structures with an exocyclic double bond are uniformly preferred in the cyclopropanes, but that the preference in the nitrogen heterocycles varies depending on X. Ring strain was evaluated with the use of homodesmotic reactions.…”
Section: Small Ring Compoundsmentioning
confidence: 99%